Interferensi Bahasa Indonesia ke dalam Bahasa Arab di Pondok Roudlatul Qur’an Metro Lampung - Amalia, Dian Risky; Hidayatullah, Rizky; Anwar, Muhammad Saidun; Irhamudin, Irhamudin (Attractive : Innovative Education Journal, 2019)
The aim of the study focuse on the interference of Indonesian into Arabic viewed from various aspects such as phonological aspects, morphology, syntax, lexicology, and the causes of such interference, namely about the first language interference of santri to their Arabic pronunciation in Rhoudhatul Qur'an Islamic Boarding School on in 2018. In essence, research is an attempt made to look deeply at the identity of the object of research. Because the object of language research cannot be present alone, without research. And the research that will be conducted is by describing the object of research. Using triangulation observation, interviews, and documentation. The findings obtained by the researcher are as follows: 1) Phonological interference occurs in the letters and letters of letters which results in deviations of meaning, Morphological interference occurs in reduplications that often occur in Indonesian, which results in reduplication in Arabic, in Arabic call it jama ', syntactic interference occurs when the word is decapitated freely in a sentence structure without knowing the elements of the language are standard or not in the rules of Indonesian, so that it adversely affects Arabic, lexicological interference occurs in compound words in Indonesian, whereas in Arabic not all words have compound words which consist of two words, semantic interference occurs in the use of language which deviates from its meaning due to differences between Indonesian and Arabic, Arabic has root words, whereas in Indonesian it does not all words have root words.2) The cause of interference is due to habits that have become cultural, tides ebb and control of language, lack of knowledge, and the difficulty of cultivating good language. Hopefully it can become a reference for further research. Key words: Interference, Indonesian, Arabic